CARBON TO NITROGEN RATIO AND NITROGENOUS WASTE ACCUMULATION IN THE INTENSIVE CATFISH (Clarias gariepinus) CULTURE - Bambang Gunadi; Enang Harris; Eddy Supriyono; Sukenda Sukenda; Tatag Budiardi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2011)
This experiment was carried out to determine the optimum C/N ratio for heterotrophic bacteria (biofloc) growth in order to control nitrogenous waste accumulation in the catfish (Clarias gariepinus) culture. Twenty fish with an initial individual size of about 50 g were stocked in fiberglass tanks which were filled with 200 L of water. Fish were fed with commercial floating fish feed with a protein level of 31%-33% (manufacturer label). The daily feeding rate was 2.5% of the fish biomass. The inoculation of commercial Bacillus sp. isolates was applied in the first day of the experiment after fish stocking in order to obtain a bacterial density in water of 106 cfu/L. Molases was suplemented daily to the tanks to adjust C/N ratio in water. Four C/N ratios, i.e. 0, 7, 14, and 21, were applied as treatments in this experiment. The results showed that molasses suplementation up to C/N ratio 14 to 21 were able to support the growth of heterotrophic bacteria and to inhibit the accumulation of total ammonia nitrogen (TAN) and nitrite in water therefore increase water quality for better growth of cultured catfish.